Performing the “Roots” and “Routes” of Cultural Identity: A Study of YouTube ‘Patriotism Pop’ in India - Pandit, Mimasha (Cultural Arts Research and Development, 2025)
Following the abrogation of article 370 in 2019 Indian public sphere became a hotbed of debate. Various mediums were deployed to make public voices heard. Opinion of the civil society expressed through newspapers, television news channels verbally opposed, and sometimes supported, the act. Marches and processions were organised against, as well as for the act. The masses were believed to be untouched by the events that unfolded. Days within the publication of the act, a series of pop songs set to folk or raunchy tunes began to flood Youtube. These songs received millions of hits every day. Songs encouraging the North Indian youth to bring brides from Kashmir became quite a YouTube sensation as did songs meeting out warnings to supposed national traitors and most importantly to the frontier arch enemy- Pakistan. Scores of comments online encouraged these online social media productions In this paper, I would like to engage with the textuality, performativity (production) of the idea that the act of abrogation propagated, and how it has had a nuanced reception (consumption) in the lives of people thereby developing a space to look at popular culture as something more than just a commercial wasteland. Another aspect of Indian political economy that I would like to interrogate through a semiotic analysis of the patriotic pop genre is the linguistic resonance that current political lingo had in the lyrics of the songs, thereby interrogating popular songs as “sites of memory” to reinvent the “roots” and the “routes” of cultural/national identity.